Everyday Resistance, Peacebuilding and State-making : Insights from 'Africa's World War' - Iñiguez de Heredia, Marta (Book collections on Project MUSE., 2017)
Everyday Resistance, Peacebuilding and State-making addresses debates on the liberal peace and the policies of peacebuilding through a theoretical and empirical study of resistance in peacebuilding contexts. Examining the case of 'Africa's World War' in the DRC, it locates resistance in the experiences of war, peacebuilding and state-making by exploring discourses, violence and everyday forms of survival as quotidian acts that attempt to challenge or mitigate such experiences. The analysis of resistance offers a possibility to bring the historical and sociological aspects of both peacebuilding and the case of the DRC, providing new nuanced understanding on these processes and the particular case. The book also makes a significant contribution to the theorisation of resistance in International Relations.